Comparative Ability to Tolerate Heat Between Thai Indigenous Chickens, Thai Indigenous Chickens Crossbred and Broilers by Using Percentage of Lymphocyte - Aengwanich, W. (International Journal of Poultry Science, 2008)
The purpose of this experiment was to compare the effects of high environmental temperatures on the percentage of lymphocytes between Thai Indigenous Chickens (TIC), Thai Indigenous Chickens Crossbred (TICC) and Broilers (BC) TIC and TICC and BC. One kilogram of male and female TIC and TICC and BC were maintained in the environmental temperature range of 26±2 and 38±2oC. Percentage of lymphocytes was investigated on days 1, 7, 14, 21 and 28 of an experimental period. The results revealed the following information: On days 1 and 28, the percentage of lymphocytes of male and female TIC, TICC and BC at 26±2 and 38±2oC was not significantly different (p>0.05). On days 7, 14 and 21 of the experimental period, the percentage of lymphocytes of the chickens at 26±2oC was significantly higher than that of chickens at 38±2oC (p<0.05). At 38±2oC, on day 7, the percentage of lymphocytes of the male and female TIC and TICC was significantly higher than the male BC (p<0.05). On day 14, the percentage of lymphocytes of the male TIC was significantly higher than the male BC (p<0.05) and on day 21 of the experimental period, the percentage of lymphocytes of the male and female TIC and TICC was significantly higher than that of the male BC (p<0.05). These phenomena indicated that the chickens maintained at high environmental temperatures, were under heat stress. Chickens adapted to high heat and the BC were less tolerant to the high heat than the TICC and TIC, respectively.